2017
DOI: 10.1371/journal.pntd.0006118
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cholera "hotspots" in Uganda: An analysis of cholera surveillance data from 2011 to 2016

Abstract: BackgroundDespite advance in science and technology for prevention, detection and treatment of cholera, this infectious disease remains a major public health problem in many countries in sub-Saharan Africa, Uganda inclusive. The aim of this study was to identify cholera hotspots in Uganda to guide the development of a roadmap for prevention, control and elimination of cholera in the country.Methodology/Principle findingsWe obtained district level confirmed cholera outbreak data from 2011 to 2016 from the Minis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…underlying cause(s) of cholera. Note that increasing risk among people living proximate to water bodies has already been documented in a number of studies [18][19][20]. Since the best fit model in our study, i.e.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 55%
See 1 more Smart Citation
“…underlying cause(s) of cholera. Note that increasing risk among people living proximate to water bodies has already been documented in a number of studies [18][19][20]. Since the best fit model in our study, i.e.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 55%
“…The hotspots near the borders suggest that cholera in Zambia is linked to cross-border movement between countries where cholera is also endemic. This was observed in Uganda [18]. Further, this suggests that a collaborative intervention program with the neighboring countries could be an effective strategy to eliminate cholera in Zambia and a step toward reduction and elimination in the region.…”
Section: Discussionmentioning
confidence: 71%
“…Although models have highlighted within-household and human-to-human transmission as the catalyst in epidemics, interventions that target community-level transmission and the environment-to-human transmission pathways remain important for cholera prevention. Regional resurgences of cholera are a contributing factor to the burden of disease globally [21,23,24,127], with notable high incidence of disease and recurrent outbreaks in the lacustrine areas of East and Central Africa [128][129][130]. Community-level or mass population strategies in areas such as this may limit the reliance on active case finding or attendance at HCFs required by case-centred approaches, and provide interventions that also target the estimated 40 to 80% of cholera cases which are asymptomatic [19,131].…”
Section: Effective Interventions To Reduce Community-level Transmissionmentioning
confidence: 99%
“…67 Similarly, a study exploring the spatial distribution of cholera using GIS and identifying associated risk factors could pinpoint high-risk areas for vaccination and WASH. A study in Uganda using a similar approach demonstrated that high-risk districts were along the border with DRC and Kenya, covering a population of 7 million or about 20% of the Ugandan population. 68…”
Section: Targeted Controlmentioning
confidence: 99%